Shopaholic & baby - Kinsella, Sophie (London, England : Bantam Press, 2007)
Becky's life is blooming! She's working at London's newest fashion store The Look, house- hunting with husband Luke (her secret wish is a shoe room)... and she's pregnant! She couldn't be more everjoyed- especially since discovering that shopping cures morning sickness. Everything has got to be perfect for her baby: from the designer nursery, to the latest, coolest pram, to the celebrity, must- have obstetrician. But when the celebrity obstetrician turns out to be Luke's glamorous, intelectual ex- girlfriend, Becky's perfect world starts to crumble. She's shopping for two...but are there three in her marriage?
Keywords: Bloomwood, Becky (Fictitious character) -- Fiction; Pregnant women -- Fiction; Shopping -- Fiction; Shopping -- Fiction; Triangles (Interpersonal relations) -- Fiction